A high-energy-density fast-charging graphite negative electrode material, a preparation method thereof, a negative electrode sheet, and a battery

CN117012936BActive Publication Date: 2026-10-16SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311096349.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2026-10-16
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

[0006]本申请的目的在于提供一种高能量密度快充石墨负极材料及其制备方法、负极片和电池,旨在解决现有的石墨负极材料不能兼顾材料的容量、首效、压实、膨胀和倍率性能等各项指标的问题

Benefits of technology

首先,本申请提供的高能量密度超级快充石墨负极材料的制备方法先使用改性沥青对石墨颗粒进行造粒,得到由硬碳/软碳复合无定形碳交联的三维网状结构粘结而成的二次颗粒,二次颗粒再使用树脂与沥青的混合物进行包覆,形成一层硬碳/软碳复合无定形碳包覆层,硬碳/软碳复合无定形碳的石墨化程度介于软碳和硬碳之间,相较于硬碳包覆层石墨化度会有一定程度提升,容量也会有一定提升。硬碳/软碳复合包覆首先可以提升包覆均匀性和致密性,树脂类的材料相对沥青而言,加热后其流动性相对较差,因此将树脂和沥青掺混后进行包覆将进一步提升包覆的均匀和包覆的致密性;其次,将树脂和沥青进行复合包覆,使得包覆层表面的缺陷相对较少,比表面积会相对较小,有利于提升材料的首效和循环性能;此外硬碳/软碳复合包覆还相对于硬碳/软碳梯度包覆可以提升包覆碳层的结构一致性和均一性,有利于提升材料的各向同性,对于材料的倍率性能提升有至关重要的影响;此外复合包覆还可以提升材料的高低温性能,树脂类硬碳材料高温性能较好,沥青类软碳材料低温性能好,将硬碳软碳进行复合包覆将进一步提升材料的高温和低温性能,得到的石墨负极材料具有高能量密度和超级快充性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117012936B_ABST
    Figure CN117012936B_ABST
Patent Text Reader

Abstract

The application provides a high-energy-density fast-charging graphite negative electrode material and a preparation method, a negative electrode sheet and a battery, and relates to the technical field of negative electrode materials. The preparation method of the graphite negative electrode material first uses modified pitch to granulate graphite particles to obtain secondary particles formed by bonding of a three-dimensional network structure crosslinked by hard carbon / soft carbon composite amorphous carbon, and then uses a mixture of resin and pitch to coat the secondary particles to form a hard carbon / soft carbon composite amorphous carbon coating layer. The graphitization degree of the hard carbon / soft carbon composite amorphous carbon is between that of soft carbon and hard carbon, and the hard carbon / soft carbon composite amorphous carbon is more easily graphitized than the hard carbon coating layer. The obtained graphite negative electrode material has high energy density and super-fast-charging performance, and can balance the capacity, initial efficiency, compaction, expansion and rate performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of anode material technology, and in particular to a high energy density fast-charging graphite anode material, its preparation method, anode sheet, and battery. Background Technology

[0002] With the rapid development of the economy and society, the increasing popularity of new energy vehicles, and the continuous iteration and upgrading of intelligent electronic products, people's demand for and technical requirements of lithium-ion batteries are also getting higher and higher. Whether for lithium-ion batteries used in new energy vehicles or electronic products, the requirements for lithium-ion batteries are roughly the same: under the premise of ensuring normal and safe use, the battery needs to have high energy density. This ensures that new energy vehicles and electronic products have a long driving range and long standby time on a single charge. At the same time, lithium-ion batteries also need to have fast-charging performance, which ensures that the battery takes a short time to fully charge, improving the user experience.

[0003] Currently, the range difference between new energy vehicles and traditional gasoline vehicles is not significant. The most crucial factor affecting the large-scale and widespread adoption of new energy vehicles is how to improve the fast-charging performance of lithium-ion batteries while maintaining high energy density and safety. When the time it takes to fully charge a new energy vehicle is roughly the same as the time it takes to fill a traditional gasoline vehicle's tank, then new energy vehicles will have a very clear advantage over gasoline vehicles. Furthermore, fast charging will greatly enhance the competitiveness and user experience of electronic products. Therefore, achieving high-speed charging while ensuring the safety and high energy density of lithium-ion batteries is a critical challenge that the entire industry urgently needs to solve.

[0004] Currently, graphite is still the most widely used anode material in the lithium-ion battery industry, accounting for more than 99% of the anode market share. Although the technology and market for graphite anodes in lithium-ion batteries are very mature, there are still many problems to be solved in the actual application of graphite anode materials, such as low specific capacity, low overpotential, easy lithium deposition during charging and discharging, poor fast charging performance, and side reaction gas generation during charging and discharging.

[0005] The fast charging issue has received widespread attention from researchers. To improve the fast charging performance of graphite materials, researchers have tried various methods. However, existing methods usually only focus on improving the rate performance of graphite anode materials. While improving rate performance, it often comes at the cost of reduced capacity, reduced first-time efficiency, increased specific surface area, reduced tap density, and increased irreversible capacity. The "barrel effect" is obvious. Therefore, if we do not consider other properties of graphite anodes, there are many methods and strategies to improve the rate performance of materials, and the effects are very obvious. However, in actual industrial applications, more consideration is given to the various performance indicators of materials. Therefore, it is very challenging and difficult to balance the capacity, first-time efficiency, compaction, expansion, and rate performance of materials in practical applications. The requirements are also very high. Summary of the Invention

[0006] The purpose of this application is to provide a high-energy-density fast-charging graphite anode material and its preparation method, anode sheet and battery, aiming to solve the problem that existing graphite anode materials cannot simultaneously achieve various indicators such as capacity, first-time efficiency, compaction, expansion and rate performance.

[0007] To achieve the above objectives, this application adopts the following technical solution: In a first aspect, this application provides a method for preparing a high-energy-density super-fast-charging graphite anode material, comprising: The pulverized coke raw material is graphitized to obtain the first precursor; Modified asphalt is obtained by mixing asphalt with a polymer modifier and treating it at a first temperature. The first precursor and the modified asphalt are mixed, granulated, and treated at a second temperature to obtain the second precursor; The resin and asphalt were mixed evenly to obtain the third precursor; The second precursor and the third precursor are mixed, carbonized at high temperature, sieved, and then graded and demagnetized to obtain the high energy density super fast charging graphite anode material.

[0008] In some embodiments, the process of graphitizing the pulverized coke raw material further includes: The first precursor is obtained by calcining a mixture of graphite particles and a pore-forming agent. After calcining the mixture of graphite particles and the pore-forming agent, porous graphite is obtained. The porous graphite has defects on its surface, which can improve the subsequent coating effect.

[0009] The graphite particles are mixed with a pore-forming agent and calcined to obtain the first precursor, which satisfies at least one of the following conditions (1)-(5): (1) The pore-forming agent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium chloride, and potassium sulfate; (2) The mass percentage of the pore-forming agent is 5%-40%; (3) The mixing time is 30-180 min, the calcination temperature is 700-1500 ℃, the heating rate is 2-10 ℃ / min, and the calcination time is 2-6 h; N2 is introduced during the calcination process, and the N2 flow rate is 2-10 mL / min; (4) The porosity B of the first precursor is 5%-15%; the average pore size C of the first precursor is 0.05-50 nm; and the pore volume D of the first precursor is 0.002-0.5 cm³. 3 The specific surface area F of the first precursor is 1-10m². 2 / g; (5) When condition (4) is met, the relationship between the capacity W of the first precursor and the porosity B and the degree of graphitization g is: W-5≤372*g+B*350≤W+5; the relationship between the porosity B and the amount of pore-forming agent A is: B*1.5≤A*5-2≤B*2.5; the relationship between the specific surface area F and the porosity B and the pore volume D is: F*1.5≤D*B*2≤F*3.

[0010] Preferably, the graphitization of the pulverized coke raw material to obtain the first precursor satisfies at least one of the following conditions (6)-(13): (6) The coke raw material is one or more of oil-based needle coke, coal-based needle coke, medium- and high-sulfur petroleum coke and graphite particles; (7) The pulverized coke raw material is first modified and then graphitized, the modification including: The pulverized coke raw material is mixed with a coke raw material modifier at a mass ratio of (80-120):1 and heat-treated at 200-500℃ for 8-15 h to obtain the modified coke raw material. (8) After satisfying condition (7), the coke raw material modifier is obtained by mixing toluene, sodium silicate, silicon dioxide and boric acid in a mass ratio of (2.5-5.5):(0.5-1.5):(1.2-2.8):(1.6-3.0); (9) After satisfying condition (7), the proportions of the sheet structure, fiber structure, mosaic structure and wide-area structure of the modified coke raw material are respectively: (34%-55%): (8.5%-20%): (14%-32%) (10%-28%). (10) The coke raw material is first coarsely crushed using a coarse crusher to small particles with a particle size of 0.2-2.5 cm. After the coarsely crushed material is dried, it is then pulverized by a pulverizing device. (11) After satisfying condition (10), the screen size of the coarse crusher is 20-80 mesh, the drying temperature is 80-150 ℃, and the drying time is 24-48 h; (12) After satisfying condition (10), the main power of the crushing equipment is 10-20 kW, the internal classification power is 15-30 kW, the feeding power is 2-8 kW, the induced draft power is 20-40 kW, and the crushing yield is >88%; (13) The graphitization temperature is 2800-3500 ℃, the graphitization time is 4-12 h, the graphitization degree g after graphitization is 92-98%, and the relationship between the graphitization degree g and the capacity E of the first precursor is: E-3≤372*g≤E+5.

[0011] Preferably, the process of mixing asphalt with a polymeric modifier and treating it at a first temperature to obtain modified asphalt satisfies at least one of the following conditions (a)-(d): (a) The polymer modifier is one or more of styrene, butadiene, chloroprene, isoprene, propylene, and acrylonitrile butadiene; (b) The mass percentage of the polymer modifier is 1%-10%; (c) The mixing time is 30-180 min, the first temperature is 200-400 ℃, and nitrogen gas is introduced during the treatment at a flow rate of 0.1-1.5 L / min; (d) The viscosity of the modified asphalt is 50-300 cp; the carbon residue of the modified asphalt is 30%-90%; the softening point of the modified asphalt is 100-350℃; and the β resin content of the modified asphalt is 20%-60%.

[0012] Preferably, the process of mixing and granulating the first precursor and the modified asphalt, and then treating them at a second temperature to obtain the second precursor satisfies at least one of the following conditions (A)-(E): (A) The mass percentage of the modified asphalt is 1%-15%; (B) The mixing time is 60-240 min, the granulation temperature is 450-800 ℃, the granulation time is 4-12 h, the rotation speed is 10-25 Hz, and N2 is introduced during the granulation process at a flow rate of 0.1-2 L / min. (C) The volatile matter content of the granulated material is 0.2%-2%, the sieving rate of the granulated material is 85%-98%, and the tap density of the granulated material is 0.4-0.9 g / cm³. 3 The specific surface area of ​​the granulated material is 0.5-5 m². 2 / g, the D50 particle size of the granulated material is 8-25μm, and the relationship between the D50 particle size P of the granulated material and the amount of modified asphalt added T is 1.2≤P-(35*T-3.45)≤5.5; (D) The second temperature is 500-800℃, the heating rate is 8-15℃ / min, the treatment time is 6-12 h, and N2 is introduced during the treatment at the second temperature at a flow rate of 1-5 L / min; (E) The specific surface area of ​​the second precursor is 0.5-3.5 m². 2 / g, the OI value of the second precursor is 2-8, and the ID / IG value of the second precursor is 1.5-5.0.

[0013] Preferably, the process of uniformly mixing the resin and asphalt to obtain the third precursor satisfies at least one of the following conditions (I)-(III): (I) The mass percentage of the resin and the asphalt is (50-80):(20-50), and the mixing time is 100-300 min; (II) The resin is one or more of phenolic resin, urea-formaldehyde resin, epoxy resin, polyurethane resin, polyester resin and polyacrylic resin, and the softening point of the asphalt is 150-350℃. (III) The carbon residue of the third precursor is 40%-90%.

[0014] Preferably, the mixing of the second precursor and the third precursor, followed by high-temperature carbonization, satisfies at least one of the following conditions (a) to (v): (i) The mixing mass ratio of the second precursor to the third precursor is (3:7) to (8:2); (ii) The mixing time between the second precursor and the third precursor is 120-300 min, and the rotation speed is 100-200 r / min; (iii) The high-temperature carbonization temperature is 1050-1600℃, the heating rate is 1-6℃ / min, and the high-temperature carbonization time is 10-24 h; (iv) The porosity of the material after high-temperature carbonization is 0.5%-2.5%, the coating thickness of the material after high-temperature carbonization is 5-100 nm, and the graphitization degree of the material after high-temperature carbonization is 93%-98%; (v) The relationship between the graphitization degree g of the material after high-temperature carbonization and the resin asphalt mixing ratio C is 320≤g*372+300*C≤400, and the relationship between the graphitization degree g of the material after high-temperature carbonization and the capacity H and the rate performance K under the 2C rate condition is 1≤[372*g / H*1.2] / K≤5.

[0015] Secondly, this application also provides a high-energy-density super-fast-charging graphite anode material prepared by the above-mentioned method for preparing high-energy-density fast-charging graphite anode material.

[0016] In some embodiments, the high energy density super-fast charging graphite anode material includes a core and a coating layer covering the core, wherein the coating layer is a hard carbon / soft carbon composite amorphous carbon, and the core is formed by bonding multiple porous graphite particles through a three-dimensional network structure of hard carbon / soft carbon composite amorphous carbon crosslinking. In some embodiments, the D50 of the high energy density super-fast charging graphite anode material is 15-17 μm, and the coating thickness is 10-50 nm.

[0017] Thirdly, this application provides a negative electrode sheet, which includes the above-mentioned high energy density super fast charging graphite negative electrode material.

[0018] Fourthly, this application provides a battery comprising the aforementioned high-energy-density super-fast charging graphite anode material or the aforementioned anode sheet.

[0019] The technical solution of this application has at least the following beneficial effects: First, the preparation method of the high energy density super fast charging graphite anode material provided in this application first uses modified asphalt to granulate graphite particles to obtain secondary particles bonded by a three-dimensional network structure of hard carbon / soft carbon composite amorphous carbon crosslinking. The secondary particles are then coated with a mixture of resin and asphalt to form a hard carbon / soft carbon composite amorphous carbon coating layer. The graphitization degree of the hard carbon / soft carbon composite amorphous carbon is between that of soft carbon and hard carbon. Compared with the hard carbon coating layer, the graphitization degree will be improved to a certain extent, and the capacity will also be improved to a certain extent. Hard / soft carbon composite coating firstly improves coating uniformity and density. Resin-based materials have relatively poor fluidity after heating compared to asphalt; therefore, mixing resin and asphalt before coating further enhances coating uniformity and density. Secondly, composite coating of resin and asphalt results in fewer defects on the coating layer surface and a smaller specific surface area, which is beneficial for improving the material's first-efficiency and cycle performance. Furthermore, compared to hard / soft carbon gradient coating, hard / soft carbon composite coating improves the structural consistency and uniformity of the coated carbon layer, which is beneficial for improving the material's isotropy and has a crucial impact on rate performance. In addition, composite coating can improve the material's high and low temperature performance. Resin-based hard carbon materials have good high-temperature performance, while asphalt-based soft carbon materials have good low-temperature performance. Composite coating of hard and soft carbon further enhances both high and low temperature performance, resulting in graphite anode materials with high energy density and super-fast charging capabilities.

[0020] Secondly, the high-energy-density super-fast charging artificial graphite anode material provided in this application exhibits a secondary particle structure. The secondary particles are composed of uniformly bonded single particles with a small number of pores between them, providing convenient channels for ion transport. A layer of hard / soft carbon composite amorphous carbon is uniformly coated on the surface of each single particle, reducing the resistance to lithium ion insertion and extraction between graphite layers and lowering the material's impedance. The secondary particles are formed by the bonding of individual particles together with hard / soft carbon composite amorphous carbon, and the surface of these secondary particles is also uniformly coated with another layer of hard / soft carbon composite amorphous carbon, resulting in a lower specific surface area, reducing side reactions between the material and the electrolyte, and lowering irreversible capacity. The double-core-shell structure composed of hard and soft carbon, while the secondary particles themselves exhibit a single-core-shell structure, makes the internal single-particle graphite cores more stable, facilitating the formation of a more stable SEI film. This structure also allows for consideration of various performance indicators of the material (capacity, compaction, rate performance, and cycle performance).

[0021] Furthermore, the preparation method of the high-energy-density super-fast charging graphite anode material in this application involves modifying the graphite particles with a pore-forming agent after obtaining the graphite particles to obtain porous graphite. This porous graphite structure increases the defects on the graphite surface, thereby increasing the bonding strength between the graphite and the coating agent. This transforms the original surface contact between the graphite and the pitch-based binder into a three-dimensional bulk phase contact, increasing the contact area between the graphite and the coating agent. This further enhances the bonding strength of the secondary graphite particles, improving the structural and mechanical strength of the material, which greatly contributes to the cycle stability of the material. Secondly, the pore-forming binder can penetrate into the bulk phase of the graphite material, increasing the ion and electron transport channels and further improving the rate performance of the material. Finally, the pores improve the wettability of the material to the electrolyte, enhancing the utilization rate of the active material. At the same time, the micropores of the porous graphite also have the effect of storing lithium ions, further increasing the capacity of the material.

[0022] Furthermore, this application establishes a coke raw material database by extensively evaluating the basic indicators of coke raw materials and establishing a correspondence between them and the structure and organization of coke raw materials. This database establishes a correlation between the structural composition of coke raw materials, their basic indicators, and the final material properties after graphitization. Based on this relationship, suitable coke raw materials for high-energy-density fast-charging artificial graphite anodes can be rapidly screened. The coke raw materials are pretreated with modifiers, and their components are analyzed and modified to control the proportion of various structural elements (sheet structure, fiber structure, mosaic structure, and wide-area structure). A higher proportion of sheet and fiber structures results in a relatively higher capacity of the obtained graphite anode material, while a higher proportion of mosaic and wide-area structures indicates better isotropy and rate performance, thus balancing the material's energy density and rate performance. Attached Figure Description

[0023] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0024] Figure 1 Here is a SEM image of the graphite anode material prepared in Example 1; Figure 2 Here is a SEM image of the graphite anode material prepared in Example 2; Figure 3 Here is a SEM image of the graphite anode material prepared in Example 3; Figure 4 Here is a SEM image of the graphite anode material prepared in Example 4; Figure 5 Here is a SEM image of the graphite anode material prepared in Example 5; Figure 6SEM image of the graphite anode material prepared in Comparative Example 1; Figure 7 SEM image of the graphite anode material prepared in Comparative Example 2; Figure 8 SEM image of the graphite anode material prepared in Comparative Example 3; Figure 9 SEM image of the graphite anode material prepared in Comparative Example 4; Figure 10 SEM image of the graphite anode material prepared in Comparative Example 5; Figure 11 This is a SEM image of the graphite anode material prepared in Comparative Example 6. Detailed Implementation

[0025] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0026] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0027] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0028] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.

[0029] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.

[0030] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0031] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0032] Example 1 The preparation method of the high energy density super-fast charging graphite anode material in Example 1 includes the following steps: Step 1: 50 kg of coal-based needle coke raw material is coarsely crushed using a coarse crusher with a 30-mesh screen to a coke raw material to a depth of 0.5 cm. The coke raw material after coarse crushing is then dried at 120 ℃ for 24 h.

[0033] Step 2: The coke raw material after coarse crushing in Step 1 is crushed using a pulverizer. The main power of the pulverizer is 15 kW, the internal classification power is 20 kW, the feeding power is 5 kW, the induced draft power is 25 kW, and the crushing yield is 90%, yielding 45 kg of crushed product.

[0034] Step 3: The material pulverized in Step 2 is graphitized at a temperature of 3300 ℃ for 8 h.

[0035] Step 4: Mix the 40.5 kg graphite particles and 4.5 kg potassium hydroxide from Step 3 for 60 min to obtain a mixture.

[0036] Step 5: The mixture from Step 4 is placed in an oven for calcination to obtain porous graphite. The calcination temperature is 900 ℃, the calcination time is 4 h, the N2 flow rate is 5 mL / min, and the heating rate is 5 ℃ / min.

[0037] Step 6: Mix 1 kg of asphalt with 50 g of ethylene butadiene for 120 min, and then heat-treat at 300 ℃ to obtain modified asphalt for 100 min.

[0038] Step 7: Take 9.85 kg of the sample from Step 5 and mix it with 0.15 kg of the modified asphalt from Step 6. The asphalt mixing ratio is 1.5%. Mix for 65 min at a speed of 280 Hz.

[0039] Step 8: Granulate the material mixed in Step 7 at a granulation temperature of 500℃ for 8 hours, a rotation speed of 15.5 Hz, an N2 flow rate of 0.2 L / min, and an asphalt softening point of 180℃.

[0040] Step 9: The mixed materials from Step 8 are subjected to high-temperature heat treatment. The high-temperature carbonization temperature is 800 ℃, the high-temperature carbonization time is 6 h, and the heating rate is 8 ℃ / min.

[0041] Step 10: Mix 700 g of phenolic resin with 300 g of asphalt for 120 min at a speed of 200 r / min.

[0042] Step 11: Mix 4.85 kg of the carbonized material obtained in Step 9 with the composite precursor material prepared in Step 10, and mix for 120 min.

[0043] Step 12: Carbonize the mixture obtained in Step 11 at 1350 °C for 16 h at a heating rate of 2.5 °C / min.

[0044] Step 13: The material carbonized at high temperature in Step 12 is sieved through a 250-mesh sieve, and then classified and demagnetized to obtain the high energy density super fast charging graphite anode material of Example 1.

[0045] Example 2 The preparation method of the high energy density super-fast charging graphite anode material in Example 2 includes the following steps: Step 1: 50 kg of coal-based needle coke raw material is coarsely crushed using a coarse crusher with a 30-mesh screen to a coke raw material to a thickness of 0.5 cm. The coke raw material after coarse crushing is then dried at 120 ℃ for 24 h.

[0046] Step 2: The coke raw material after coarse crushing in Step 1 is crushed using a pulverizer. The main power of the pulverizer is 15 kW, the internal classification power is 20 kW, the feeding power is 5 kW, the induced draft power is 25 kW, and the crushing yield is 90%, yielding 45 kg of crushed product.

[0047] Step 3: The material pulverized in Step 2 is graphitized to obtain graphite particles. The graphitization temperature is 3300 ℃ and the graphitization time is 8 h.

[0048] Step 4: Mix 1 kg of asphalt with 50 g of ethylene butadiene for 120 min, and then heat-treat at 300 ℃ to obtain modified asphalt for 100 min.

[0049] Step 5: Take 9.85 kg of the sample from Step 3 and mix it with 0.15 kg of the modified asphalt from Step 4. The asphalt mixing ratio is 1.5%. Mix for 65 min at a speed of 280 Hz.

[0050] Step Six: Granulate the material mixed in Step Five. The granulation temperature is 500 ℃, the granulation time is 8 h, the rotation speed is 15.5 Hz, the N2 flow rate is 0.2 L / min, and the asphalt softening point is 180 ℃.

[0051] Step 7: The mixed materials from Step 6 are subjected to high-temperature heat treatment. The high-temperature carbonization temperature is 800 ℃, the high-temperature carbonization time is 6 h, and the heating rate is 8 ℃ / min.

[0052] Step 8: Mix 700 g of phenolic resin with 300 g of asphalt for 120 min at a speed of 200 r / min.

[0053] Step 9: Mix 4.85 kg of the carbonized material obtained in Step 7 with the composite precursor material prepared in Step 8, and mix for 120 min.

[0054] Step 10: Carbonize the mixture obtained in Step 9 at 1350 ℃ for 16 h at a heating rate of 2.5 ℃ / min.

[0055] Step 11: The material carbonized at high temperature in Step 10 is sieved through a 250-mesh sieve, and then classified and demagnetized to obtain the high energy density super fast charging graphite anode material of Example 2.

[0056] Example 3 The preparation method of the high energy density super-fast charging graphite anode material in Example 3 includes the following steps: Step 1: 50 kg of coal-based needle coke raw material is coarsely crushed using a coarse crusher with a 30-mesh screen to a coke raw material to a depth of 0.5 cm. The coke raw material after coarse crushing is then dried at 120 ℃ for 24 h.

[0057] Step 2: The coke raw material after coarse crushing in Step 1 is crushed using a pulverizer. The main power of the pulverizer is 15 kW, the internal classification power is 20 kW, the feeding power is 5 kW, the induced draft power is 25 kW, and the crushing yield is 90%, yielding 45 kg of crushed product.

[0058] Step 3: Add coke raw material modifier to the crushed coke raw material. The coke raw material modifier is obtained by mixing toluene, sodium silicate, silicon dioxide and boric acid in a mass ratio of 5:1:2:2. Take 45 kg of coke raw material, add 0.45 kg of coke raw material modifier, and heat treat at 300 ℃ for 12 h to obtain 42.6 kg of modified coke raw material. The proportions of the obtained coke raw material with lamellar structure, fibrous structure, mosaic structure and wide-area structure are 45%, 15%, 22% and 18%, respectively.

[0059] Step 4: The coke raw material modified in Step 3 is graphitized at a temperature of 3300 ℃ for 8 h.

[0060] Step 5: Mix the 40.5 kg graphite particles and 4.5 kg potassium hydroxide from Step 4 for 60 min to obtain a mixture.

[0061] Step Six: The mixture from Step Five is placed in an oven for calcination to obtain porous graphite. The calcination temperature is 900 ℃, the calcination time is 4 h, the N2 flow rate is 5 mL / min, and the heating rate is 5 ℃ / min.

[0062] Step 7: Mix 1 kg of asphalt with 50 g of ethylene butadiene for 120 min, and then heat-treat at 300 ℃ to obtain modified asphalt for 100 min.

[0063] Step 8: Take 9.85 kg of the sample from Step 6 and mix it with 0.15 kg of the modified asphalt from Step 6. The asphalt mixing ratio is 1.5%. Mix for 65 min at a speed of 280 Hz.

[0064] Step 9: Granulate the material mixed in Step 8 at a temperature of 500℃ for 8 hours, a rotation speed of 15.5 Hz, a flow rate of N2 of 0.2 L / min, and an asphalt softening point of 180℃.

[0065] Step 10: The mixed materials from Step 9 are subjected to high-temperature heat treatment. The high-temperature carbonization temperature is 800 ℃, the high-temperature carbonization time is 6 h, and the heating rate is 8 ℃ / min.

[0066] Step 11: Mix 700 g of phenolic resin with 300 g of asphalt for 120 min at a speed of 200 r / min.

[0067] Step 12: Mix 4.85 kg of the carbonized material obtained in Step 10 with the composite precursor material prepared in Step 11, and mix for 120 min.

[0068] Step 13: Carbonize the mixture obtained in Step 12 at 1350 °C for 16 h at a heating rate of 2.5 °C / min.

[0069] Step Fourteen: The material carbonized at high temperature in Step Thirteen is sieved through a 250-mesh sieve, and then graded and demagnetized to obtain the high energy density super fast charging graphite anode material of Example 3.

[0070] Example 4 In Example 1, potassium hydroxide in step four was replaced with potassium chloride, and the remaining steps were the same as in Example 1.

[0071] Example 5 The coal-based coke in step one of Example 1 was replaced with graphite granules, and the remaining steps were the same as in Example 1.

[0072] Comparative Example 1 Replace the modified asphalt used for granulation in step seven with conventional asphalt that has not been treated with polymer modifiers, and the remaining steps are the same as in Example 1.

[0073] Comparative Example 2 After obtaining the secondary particles after high-temperature carbonization in step nine, no further mixing and coating with resin and asphalt is performed; the remaining steps are the same as in Example 1.

[0074] Comparative Example 3 After obtaining the secondary particles after high-temperature carbonization in step nine, only 1000 g of phenolic resin is used for coating, and the remaining steps are the same as in Example 1.

[0075] Comparative Example 4 After obtaining the secondary particles after high-temperature carbonization in step nine, only 1000 g of asphalt is used for coating, and the remaining steps are the same as in Example 1.

[0076] Comparative Example 5 After obtaining the secondary particles after high-temperature carbonization in step nine, they are first coated with 700 g of phenolic resin, and then coated with 300 g of asphalt. The remaining steps are the same as in Example 1.

[0077] Comparative Example 6 The porous graphite obtained in step five is first granulated using a mixture of phenolic resin and asphalt, and then coated with the modified asphalt from step six. The remaining steps are the same as in Example 1.

[0078] The specific surface area, specific capacity, tap density, compaction density, and first-efficiency test results of the graphite anode materials obtained in Examples 1 to 5 and Comparative Examples 1 to 6 are shown in Table 1.

[0079] Table 1. Performance indicators of graphite anode materials in different embodiments and comparative examples. As shown in Table 1, the graphite anode material obtained by adopting the scheme of this application has higher isotropy, higher tap density, better capacity, first-efficiency, compaction and cycle performance, more uniform surface coating, denser surface coating layer and granulation structure, fewer pores and defects on the material surface, and relatively fewer side reactions when in contact with electrolyte. In addition, the internal structure of the material is more dense and stronger, and the overall uniformity of the material is better. This also makes it exhibit better electrochemical performance. The design process of the product determines the structure of the material, and the structure of the material determines the performance of the material.

[0080] In Example 2, no pores were created in the graphite particles compared to Example 1, resulting in a decrease in both the specific capacity and initial efficiency of the obtained graphite anode material, demonstrating that porous graphite can improve the performance of graphite anode materials. In contrast, in Example 3, the coke raw material was modified compared to Example 1, resulting in an increase in both the specific capacity and initial efficiency of the obtained graphite anode material, demonstrating that the modified coke raw material can further improve the performance of graphite anode materials.

[0081] Comparative Example 7 The amount of phenolic resin added in step ten was changed, while the remaining steps were the same as in Example 1. The effects of different resin addition amounts on the morphology, specific surface area, specific capacity, and first-efficiency of the coated graphite are shown in Table 2.

[0082] Table 2 Effect of resin addition amount on the morphology of graphite anode after carbonization In the graphite coating process, the addition of reagents such as water-soluble phenolic resin and urea-formaldehyde resin mainly plays a coating role. Coating can reduce the specific surface area of ​​the material and improve the first efficiency. In particular, the carbonization of natural graphite through coating can reduce the expansion during charge and discharge, effectively improving the stability and cycle performance of the material. At the same time, coating can improve the compatibility with propylene carbonate (PC) based electrolytes, which greatly improves the reversible capacity and rate performance of the material. Therefore, the coating process has a crucial impact on the performance of graphite anodes.

[0083] Table 2 shows that with the increase of resin addition, the specific surface area of ​​the synthesized coated carbonized graphite sample first decreases and then increases, while the specific capacity of the material used in coin cells also first increases and then decreases. This is because with the increase of resin coating, some voids and defects on and inside the graphite anode are filled by amorphous carbon, reducing the specific surface area. Therefore, the initial efficiency of the synthesized coated carbonized graphite anode material increases, and the sphericity of the final coated carbonized material also increases with the increase of coating amount. When the coating amount is 700 g, the specific surface area is the smallest, the specific capacity is the largest, and the initial efficiency is also the highest. Once the amount of coating agent exceeds 700 g, the specific surface area increases with the increase of coating amount.

[0084] The main reasons for this are as follows: Although the coating resin can reduce the specific surface area of ​​the material by entering the voids and reducing surface defects during carbonization, the coating thickness on the material surface also increases with the increase in coating amount. Once the voids and defects on the material surface are completely filled and wrapped by the coated carbon, the excess residual carbon will further generate new coating layers on its surface. These new coating layers are all amorphous carbon. Therefore, with the increase of amorphous carbon, the specific surface area of ​​the material will increase again, and the porosity and defects on the surface will also increase. This will greatly increase the irreversible capacity of the material, resulting in a decrease in the specific capacity and first-efficiency of the material. Therefore, the amount of resin coating has a direct impact on the final morphology, specific surface area and electrochemical performance of the material.

[0085] Comparative Example 8 The temperature of the carbonization coating in step 12 was changed, while the remaining steps were the same as in Example 1. The effects of different carbonization coating temperatures on the morphology, specific surface area, specific capacity, and first-efficiency of the graphite anode are shown in Table 3.

[0086] Table 3. Effect of coating carbonization temperature on the electrochemical performance of graphite anode materials. In the process of graphite anode coating and carbonization, the high-temperature carbonization process mainly involves treating the resin coated on the graphite surface at high temperature to obtain amorphous carbon-coated graphite anode. During the high-temperature carbonization process, the carbonization temperature has a significant impact on the morphology and electrochemical performance of the final graphite product. When the coated material is carbonized at high temperature, the volatiles in the material will gradually be released. Therefore, as the carbonization temperature increases, the residual carbon content on the graphite surface decreases. Thus, a reasonable carbonization temperature has a crucial impact on the amount of residual carbon on the graphite surface after coating and carbonization.

[0087] As shown in Table 3, with the increase of carbonization temperature, the specific surface area of ​​the coated carbonized graphite first decreases and then increases. When the carbonization temperature is 1250 ℃, the specific surface area of ​​the coated carbonized graphite anode is the smallest. When the temperature exceeds 1250 ℃, the specific surface area of ​​the prepared coated carbonized graphite increases with the increase of carbonization temperature.

[0088] During high-temperature carbonization, within a certain temperature range, the specific surface area of ​​the coated graphite increases with increasing carbonization temperature. If the carbonization temperature is too high, the amount of residual carbon on the graphite surface will decrease, resulting in a thinner carbon coating layer. Areas with more defects on the graphite surface may not be completely coated with carbon, thus increasing the specific surface area of ​​the coated material. When the carbonization temperature is too low, the carbonization of the coating precursor is incomplete, resulting in an excessively thick carbon coating layer after carbonization, leading to an increase in surface defects and affecting the electrochemical performance of the material. The specific capacity also decreases accordingly, and the initial efficiency is reduced.

[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

[0090] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, in the foregoing claims, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a high-energy-density fast-charging graphite anode material, characterized in that, include: The pulverized coke raw material is graphitized, and the graphite particles are mixed with a pore-forming agent and calcined to obtain the first precursor. The coke raw material is one or more of oil-based needle coke, coal-based needle coke, medium-high sulfur petroleum coke, and graphite particles; the pore-forming agent is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, potassium chloride, and potassium sulfate. Modified asphalt is obtained by mixing asphalt with a polymeric modifier and treating it at a first temperature; the polymeric modifier is one or more of styrene, butadiene, chloroprene, isoprene, propylene, and acrylonitrile butadiene. The first precursor and the modified asphalt are mixed, granulated, and treated at a second temperature to obtain the second precursor; The resin and asphalt are mixed evenly to obtain a third precursor; the resin is one or more of phenolic resin, urea-formaldehyde resin, epoxy resin, polyurethane resin, polyester resin and polyacrylic acid resin. The second precursor and the third precursor are mixed, carbonized at high temperature, sieved, and then graded and demagnetized to obtain the high energy density fast-charging graphite anode material.

2. The method for preparing the high energy density fast-charging graphite anode material according to claim 1, characterized in that, At least one of the following conditions (1)-(4) must be met: (1) The mass percentage of the pore-forming agent is 5%-40%; (2) The mixing time is 30-180 min, the calcination temperature is 700-1500 ℃, the heating rate is 2-10℃ / min, and the calcination time is 2-6 h; N2 is introduced during the calcination process, and the N2 flow rate is 2-10 mL / min; (3) The porosity B of the first precursor is 5%-15%; the average pore size C of the first precursor is 0.05-50 nm; and the pore volume D of the first precursor is 0.002-0.5 cm. 3 The specific surface area F of the first precursor is 1-10 m². 2 / g; (4) When condition (3) is met, the relationship between the capacity W, porosity B, and graphitization degree g of the first precursor is: W-5≤372 g+B 350≤W+5; The relationship between the porosity B and the amount of pore-forming agent A added is: B 1.5≤A 5-2≤B 2.5; The relationship between the specific surface area F, porosity B, and pore volume D is as follows: F 1.5≤D B 2≤F 3.

3. The method for preparing the high energy density fast-charging graphite anode material according to claim 1, characterized in that, The graphitization of the pulverized coke raw material yields a first precursor that satisfies at least one of the following conditions (6)-(12): (6) The pulverized coke raw material is first modified and then graphitized, the modification including: The pulverized coke raw material is mixed with a coke raw material modifier at a mass ratio of (80-120):1 and heat-treated at 200-500℃ for 8-15 h to obtain the modified coke raw material. (7) After satisfying condition (6), the coke raw material modifier is obtained by mixing toluene, sodium silicate, silicon dioxide and boric acid in a mass ratio of (2.5-5.5):(0.5-1.5):(1.2-2.8):(1.6-3.0); (8) After satisfying condition (6), the proportions of the sheet structure, fiber structure, mosaic structure and wide-area structure of the modified coke raw material are respectively: (34%-55%): (8.5%-20%): (14%-32%): (10%-28%). (9) The coke raw material is first coarsely crushed using a coarse crusher to small particles with a particle size of 0.2-2.5 cm. After the coarsely crushed material is dried, it is then pulverized by a pulverizing device. (10) After satisfying condition (9), the screen size of the coarse crusher is 20-80 mesh, the drying temperature is 80-150 ℃, and the drying time is 24-48 h; (11) After satisfying condition (9), the main power of the crushing equipment is 10-20 kW, the internal classification power is 15-30 kW, the feeding power is 2-8 kW, the induced draft power is 20-40 kW, and the crushing yield is >88%; (12) The graphitization temperature is 2800-3500 ℃, the graphitization time is 4-12 h, the degree of graphitization g after graphitization is 92-98%, and the relationship between the degree of graphitization g and the capacity E of the first precursor is: E-3≤372 g≤E+5.

4. The method for preparing the high energy density fast-charging graphite anode material according to claim 1, characterized in that, The process of mixing asphalt with a polymeric modifier and treating it at a first temperature to obtain modified asphalt that satisfies at least one of the following conditions (a)-(c): (a) The mass percentage of the polymer modifier is 1%-10%; (b) The mixing time is 30-180 min, the first temperature is 200-400 ℃, and nitrogen gas is introduced during the treatment at a flow rate of 0.1-1.5 L / min; (c) The modified asphalt has a viscosity of 50-300 cp; a carbon residue of 30%-90%; a softening point of 100-350℃; and a β resin content of 20%-60%.

5. The method for preparing the high energy density fast-charging graphite anode material according to claim 1 or 4, characterized in that, The process of mixing and granulating the first precursor and the modified asphalt, and then treating them at a second temperature to obtain a second precursor that satisfies at least one of the following conditions (A)-(E): (A) The mass percentage of the modified asphalt is 1%-15%; (B) The mixing time is 60-240 min, the granulation temperature is 450-800 ℃, the granulation time is 4-12 h, the rotation speed is 10-25 Hz, and N2 is introduced during the granulation process at a flow rate of 0.1-2 L / min. (C) The volatile matter content of the granulated material is 0.2%-2%, the sieving rate of the granulated material is 85%-98%, and the tap density of the granulated material is 0.4-0.9 g / cm³. 3 The specific surface area of ​​the granulated material is 0.5-5 m². 2 / g, the D50 particle size of the granulated material is 8-25μm, and the relationship between the D50 particle size P of the granulated material and the amount of modified asphalt added T is 1.2≤P-(35 T-3.45)≤5.5; (D) The second temperature is 500-800℃, the heating rate is 8-15℃ / min, the treatment time is 6-12 h, and N2 is introduced during the treatment at the second temperature at a flow rate of 1-5 L / min; (E) The specific surface area of ​​the second precursor is 0.5-3.5 m². 2 / g, the OI value of the second precursor is 2-8, and the ID / IG value of the second precursor is 1.5-5.

0.

6. The method for preparing the high energy density fast-charging graphite anode material according to claim 1, characterized in that, The resin and asphalt are mixed evenly to obtain a third precursor that satisfies at least one of the following conditions (I)-(III): (I) The mass percentage of the resin and the asphalt is (50-80):(20-50), and the mixing time is 100-300 min; (II) The softening point of the asphalt is 150-350℃; (III) The carbon residue of the third precursor is 40%-90%.

7. The method for preparing the high energy density fast-charging graphite anode material according to claim 1, characterized in that, The mixing of the second precursor and the third precursor, followed by high-temperature carbonization, satisfies at least one of the following conditions (i)-(v): (i) The mixing mass ratio of the second precursor to the third precursor is (3:7) to (8:2); (ii) The mixing time between the second precursor and the third precursor is 120-300 min, and the rotation speed is 100-200 r / min; (iii) The high-temperature carbonization temperature is 1050-1600℃, the heating rate is 1-6℃ / min, and the high-temperature carbonization time is 10-24 h; (iv) The porosity of the material after high-temperature carbonization is 0.5%-2.5%, the coating thickness of the material after high-temperature carbonization is 5-100 nm, and the graphitization degree of the material after high-temperature carbonization is 93%-98%; (v) The relationship between the degree of graphitization g of the material after high-temperature carbonization and the resin asphalt blending ratio C is 320≤g 372+300 C≤400, the relationship between the degree of graphitization g of the material after high-temperature carbonization and the capacity H and the rate performance K under the 2C coin cell rate condition is 1≤[372] g / H 1.2] / K≤5.

8. The high energy density fast-charging graphite anode material prepared by the preparation method of the high energy density fast-charging graphite anode material according to any one of claims 1 to 7.

9. The high energy density fast-charging graphite anode material according to claim 8, characterized in that, The high-energy-density fast-charging graphite anode material satisfies at least one of the following conditions (vi)-(vii): (vi) The high energy density fast-charging graphite anode material includes a core and a coating layer covering the core. The coating layer is a hard carbon / soft carbon composite amorphous carbon. The core is formed by bonding multiple porous graphite particles through a three-dimensional network structure of hard carbon / soft carbon composite amorphous carbon. (vii) The D50 of the high energy density fast-charging graphite anode material is 15-17 μm, and the thickness of the coating layer is 10-50 nm.

10. A negative electrode, said negative electrode comprising the high energy density fast-charging graphite negative electrode material as described in claim 8 or 9.

11. A battery comprising the high energy density fast-charging graphite anode material of claim 8 or 9 or the anode sheet of claim 10.

Citation Information

Patent Citations

  • Graphite-based composite negative electrode material and preparation method and application thereof

    CN115347176A

  • Soft carbon particle for negative electrode material of lithium ion battery and preparation method of soft carbon particle

    CN115566155A